The crystal structure of the double salt potassium 1-methylpiperazine-1,4-di-ium trinitrate, C5H14KN5O9 - Shang Yi-Ping; Wu Jun-Ying; Yao Yu-Le; Liu Rui-Zheng; Liu Dan-Yang; Chen Lang (Zeitschrift für Kristallographie - New Crystal Structures)
C5H14KN5O9, orthorhombic, Pbca (no. 61), a = 10.4760(3) Å, b = 14.0476(4) Å, c = 17.3708(5) Å, V = 2,556.33(13) Å3, Z = 8, T = 100 K, Rgt(F) = 0.0226, wRref(F2) = 0.0607.